2018
DOI: 10.1002/lipd.12016
|View full text |Cite
|
Sign up to set email alerts
|

Dietary High‐Oleic Acid Soybean Oil Dose Dependently Attenuates Egg Yolk Content of n‐3 Polyunsaturated Fatty Acids in Laying Hens Fed Supplemental Flaxseed Oil

Abstract: Chickens can hepatically synthesize eicosapentaenoic acid (20:5 n-3) and docosahexaenoic acid (22:6 n-3) from α-linolenic acid (ALA; 18:3 n-3); however, the process is inefficient and competitively inhibited by dietary linoleic acid (LNA; 18:2 n-6). In the present study, the influence of dietary high-oleic acid (OLA; 18:1 n-9) soybean oil (HOSO) on egg and tissue deposition of ALA and n-3 polyunsaturated fatty acids (PUFA) synthesized from dietary ALA was investigated in laying hens fed a reduced-LNA base diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 48 publications
3
30
1
Order By: Relevance
“…The lower liver concentration of ALA and SDA may be attributed at least partially to greater elongation and desaturation activity of liver enzymes or differences in liver export (Gregory et al, 2011). We have previously observed that maximal VLCn-3 PUFA enrichment was achieved when laying hens were fed diets containing 10-20 g/kg of a high-ALA FLAX oil (Elkin et al, 2018), which is similar to what we observed in broilers in the current experiment. At the higher feeding rate (e.g., 22.5 g/kg diet), AHI and FLAX increased total VLCn-3 FA contents in breast and thigh by over 1.7-fold compared to that of CON-fed birds.…”
Section: Discussionsupporting
confidence: 89%
“…The lower liver concentration of ALA and SDA may be attributed at least partially to greater elongation and desaturation activity of liver enzymes or differences in liver export (Gregory et al, 2011). We have previously observed that maximal VLCn-3 PUFA enrichment was achieved when laying hens were fed diets containing 10-20 g/kg of a high-ALA FLAX oil (Elkin et al, 2018), which is similar to what we observed in broilers in the current experiment. At the higher feeding rate (e.g., 22.5 g/kg diet), AHI and FLAX increased total VLCn-3 FA contents in breast and thigh by over 1.7-fold compared to that of CON-fed birds.…”
Section: Discussionsupporting
confidence: 89%
“…(2017) Canada 5 40 Lohmann white 19 56 Barley + SBM hemp seed oil, hemp omega 0-80 Diet 25 Huang et al. (2018) UK 4 72 White Leghorn 58 56 Corn + SBM flaxseed 0-225 Diet 26 Westbrook and Cherian (2019) UK 4 72 Brown layer 51 120 Corn + SBM flaxseed 0-10 Diet 27 Elkin et al. (2018) USA 16 100 Hy-Line W36 18 84 Corn + SBM sunflower oil, flaxseed oil 0-50 Diet 28 Moran et al.…”
Section: Methodsmentioning
confidence: 99%
“…Like humans, chickens have a limited ability to synthesize VLC n-3 PUFA from ALA or stearidonic acid ( SDA : 18:4 n-3), the desaturation product of ALA ( Fraeye et al, 2012 ; Elkin et al, 2015 , 2016 ; El-Zenary et al, 2021 ) and egg and tissue contents of DHA can be more readily enriched by direct dietary supplementation of DHA-rich ingredients ( Leskanich and Noble, 1997 ; Cachaldora et al, 2008 ; Fraeye et al, 2012 , Ribeiro et al, 2013 , Elkin et al, 2015 ; Neijat et al, 2017 ). It is also probable that, as in the rat ( Tu et al, 2010 ), VLC n-3 PUFA synthesis in chickens is regulated more by substrate levels than gene expression ( Elkin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A second objective was to observe the effect of the dietary DHA-rich MAO on hen performance and the expression of key genes related to VLDL and triglyceride synthesis and secretion. Lastly, based on prior studies in our laboratory which showed that co-feeding hens a high-oleic acid ( OLA ; 18:1 n-9) oil along with either a high-ALA flaxseed oil or a high-SDA soybean oil, attenuated egg yolk and tissue n-3 PUFA contents compared to feeding the ALA-rich or SDA-rich oils alone ( Elkin et al, 2018 , 2021 ), 2 additional diets were included in which high-OLA sunflower oil ( HOSO ) was co-fed with the high-DHA MAO.…”
Section: Introductionmentioning
confidence: 99%